Development and organisation of an effective elite sport policy system in a small state: a case study of Slovenia - Horvat, C. (2021)
Despite being a state small in population, geographical size and GDP (Thorhallsson, 2006), Slovenia tends to do well in medal rankings per GDP and per capita at the Olympic Games. To understand the influences of success of Slovene elite sport, it is important to investigate the elite sports policy system in Slovenia. Thus, this study set out to explore the contemporary structure of the elite sport policy in Slovenia, as well as the extent to which the SPLISS pillars can act as a framework for explanation of the Slovene system and to identify what other factors need to be added to this framework to better account for the characteristics of Slovenia. SPLISS was identified as the primary analytical model in the study as it is the leading model in elite sport policy analysis (Andersen, Houlihan, & Ronglan, 2015b). However, SPLISS is intended to be used as a comparative tool of elite sport policy between states (De Bosscher, Shibli, Westerbeek, & Van Bottenburg, 2015), but was not used as such in the study of a single case. Instead, SPLISS served as framework that has utility within the study as a starting point for data collection and analysis. A bioecological model was introduced to supplement the SPLISS framework as an analytical lens to account for the influences of success not considered within the SPLISS pillars. The study made a contribution because it provided an in-depth case-study of one setting which examined a small state and illustrated that there may be policy and practice variations that are a result of the specific context of the state within which the system operates. The development and structure of elite policy systems in a small state of Slovenia with limited population and GDP reflects the contextual characteristics in order to maximise success. The research adopted a qualitative approach within a case-study research design. A multi-method data collection approach was undertaken. This included documentary analysis of 43 sport policy and sport policy related documents as well as six one-time one-to-one interviews with key stakeholders within elite sport in Slovenia in order to gain an in-depth understanding of the elite sport policy system in Slovenia. A thematic analysis of the data revealed that the elite sports system in the small state of Slovenia is determined by the size and the context of the state. As highlighted by participants and in the documents, GDP and population size, as well as the historical development, culture and natural environment also influence the elite sports policy system in Slovenia. While these context specific factors limit and determine the routes taken to develop international sporting success, they also allow for adaptation and flexibility to create strategic advantages that may not be possible in different contexts. The findings also indicate that in Slovenia the elite sport system is fully integrated within the wider sports system and does not exercise a priority position over recreational sport. In fact, both recreational and elite sport are identified as priorities of the sports system. Thus, elite sport is not separate, but mutually dependent on recreational sport where there is reciprocity between the systems. Furthermore, the findings revealed that the SPLISS model was useful but not sufficient for examining the elite sport policy system in Slovenia. While all nine SPLISS pillars were vital in identifying the positive influences of international sporting success, not all factors that were derived from the data that were specific to Slovenia were accounted for within SPLISS. Moreover, some of the existing SPLISS pillars proved to be too narrowly defined to fully encompass the success factors of the Slovene elite sports system. For these reasons, additional `non-SPLISS` influences of the system were identified separately using the bioecological model, while some influences not accounted for in any of the analytical models were identified as well. Through the study it was proposed that an adapted version of the SPLISS model to better reflect the small state context of Slovenia could be developed based on four particular adaptations. Adaptation 1 proposed consideration that the influence of Pillar 2 on other pillars in the context of Slovene elite sport policy system is perceived higher than the influence of Pillar 1. Secondly, Adaptation 2 proposed the inclusion of the macro-level related influences, including historical characteristics, cultural characteristics, characteristics of the natural environment and scale characteristics. Characteristics of history and culture of Slovenia were identified through the bioecological lens. The climate and geographical characteristics within the domain of the natural environment were included in Pillar 6. Furthermore, Adaptation 3 also suggested broadening the original SPLISS Pillar 5 to consider the importance and impact of the primary environment of the athlete, specifically family support, which is considered within micro-level factors. Lastly, Adaptation 4 recommended including other influences of Slovene sporting success that could not be identified by applying SPLISS or bioecological lenses. These included independence, international sports environment and ongoing challenges within the elite sport policy system in Slovenia.